2017
DOI: 10.1002/phar.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Considerations in the Management of Patients Receiving Left Ventricular Percutaneous Mechanical Circulatory Support

Abstract: Percutaneous mechanical circulatory support (MCS) devices, including the intraaortic balloon pump, Impella, and TandemHeart, are often used for hemodynamic support in the setting of refractory cardiogenic shock. The thrombotic and bleeding complications associated with these devices is well recognized, and the Impella and TandemHeart devices have unique anticoagulation considerations that may influence patient outcomes. Both devices typically require use of a heparinized purge solution in combination with intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Consistent with our expectations, we found that practices varied considerably, even among this cohort of high-volume centers. This is not surprising given that the anticoagulation strategies used in clinical trials are often unclear or have varied across studies [8]. For example, in the ISAR-SHOCK trial comparing the Impella device to IABP in patients with cardiogenic shock after myocardial infarction, a dextrose-only purge solution was used and IV UFH was titrated to target an aPTT of 60-80 seconds [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our expectations, we found that practices varied considerably, even among this cohort of high-volume centers. This is not surprising given that the anticoagulation strategies used in clinical trials are often unclear or have varied across studies [8]. For example, in the ISAR-SHOCK trial comparing the Impella device to IABP in patients with cardiogenic shock after myocardial infarction, a dextrose-only purge solution was used and IV UFH was titrated to target an aPTT of 60-80 seconds [3].…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of UFH to the peripheral circulation also results in systemic drug exposure [8]. However, the extent to which the purge solution contributes to systemic anticoagulation can vary, thus concurrent administration of intravenous (IV) UFH is also recommended (goal activated clotting time of 160-180 seconds) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The clinical implications of these faster flow rates are largely unelucidated, but lower concentrations of heparin have been recommended despite manufacturer standards of 50 units/mL. 4 In a recent publication, Dietrich and Kazmi discuss a retrospective cohort analysis of 12 patients evaluating heparin 50 units/mL in D5W versus heparin 50 units/mL in D20W. 5 No differences were observed between D5W and D20W with regard to supratherapeutic aPTT, reduction in heparin concentration, or bleeding events although all the rates were nonsignificantly higher in the D5W cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may require supplemental heparin while others have the risk of over anticoagulation with the purge solution alone. 4 To optimize anticoagulation, clinicians have the option to reduce the concentration of heparin in the purge solution. Although the manufacturer recommends a concentration of heparin 50 units/ mL, very little information is available to support the use of a specific heparin concentration, and alternative concentrations have been proposed based on small case series.…”
Section: Introductionmentioning
confidence: 99%